2010
DOI: 10.1016/j.bbadis.2010.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Niemann–Pick type C cells show cholesterol dependent decrease of APP expression at the cell surface and its increased processing through the β-secretase pathway

Abstract: The link between cholesterol and Alzheimer's disease has recently been revealed in Niemann Pick type C disease. We found that NPC1-/- cells show decreased expression of APP at the cell surface and increased processing of APP through the β-secretase pathway resulting in increased C99, sAPPβ and intracellular Aβ40 levels. This effect is dependent on increased cholesterol levels, since cholesterol depletion reversed cell surface APP expression and lowered Aβ/C99 levels in NPC1-/- cells to the levels observed in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 42 publications
4
25
0
Order By: Relevance
“…In addition, a 3-fold increase of cholesterol was detected in the isolated lysosomal fractions from NPC1-null compared to CHOwt cells (p<0.01) ( Figure 1C). This result is in agreement with our previous work using this model (7)(8)(9). We next performed MS-based proteomic analysis of the isolated lysosomal fractions.…”
Section: Lysosomal Isolation From Npc1-null and Chowt Cells Using Thesupporting
confidence: 92%
See 2 more Smart Citations
“…In addition, a 3-fold increase of cholesterol was detected in the isolated lysosomal fractions from NPC1-null compared to CHOwt cells (p<0.01) ( Figure 1C). This result is in agreement with our previous work using this model (7)(8)(9). We next performed MS-based proteomic analysis of the isolated lysosomal fractions.…”
Section: Lysosomal Isolation From Npc1-null and Chowt Cells Using Thesupporting
confidence: 92%
“…To test these two possibilities we measured the levels of fluorescein signal in the cell lysate and in the medium 24 hours after initial uptake. We did not observe significant differences of the intracellular and Table 1 and Notably, in our previous studies we have substantially used this NPC disease cellular model to elucidate the molecular and cellular details of an AD-like phenotype in NPC (7)(8)(9)36). Based on our results we speculate that changes in the N-glycome of the lysosomal membrane proteins may contribute to lysosomal (dys)function in NPC disease.…”
Section: Lysosomal Isolation From Npc1-null and Chowt Cells Using Thesupporting
confidence: 53%
See 1 more Smart Citation
“…Aberrant Ab metabolism is at the core of pathological events in Alzheimer's disease (AD), where small Ab oligomers are believed to exert synaptotoxicity and insoluble Ab fibrils are deposited in extracellular plaques (Querfurth and LaFerla 2010;Zetterberg et al 2010). In accordance with our recent in vivo patient data, experimental studies have indicated altered amyloid metabolism in NPC (Jin et al 2004), which is influenced by cholesterol accumulation Malnar et al 2010), and might be related to development of pathology (Kodam et al 2010). The increased CSF Ab concentration is a unique finding, which has not been described in any other disease.…”
Section: Introductionmentioning
confidence: 66%
“…Loss of either NPC1 function (95% of the cases) or NPC2 function leads to accumulation and retention of cholesterol and glycolipids in late endosomes and lysosomes in visceral organs and in the brain with resultant clinical pathology. Cholesterol storage may secondarily promote neuropathology by altering processing of the β-amyloid precursor protein (APP) leading to increased formation of amyloid-β (Aβ) peptide [60].…”
Section: Niemann-pick C Disease (Np-c)mentioning
confidence: 99%